2015
DOI: 10.1016/j.neuroimage.2015.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Dual-echo fMRI can detect activations in inferior temporal lobe during intelligible speech comprehension

Abstract: The neural basis of speech comprehension has been investigated intensively during the past few decades. Incoming auditory signals are analysed for speech-like patterns and meaningful information can be extracted by mapping these sounds onto stored semantic representations. Investigation into the neural basis of speech comprehension has largely focused on the temporal lobe, in particular the superior and posterior regions. The ventral anterior temporal lobe (vATL), which includes the inferior temporal gyrus (IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 58 publications
(120 reference statements)
4
51
0
Order By: Relevance
“…As a result, the combined fMRI signal has a better contrast-to-noise ratio mainly due to the reduction in thermal noise, which can be exploited for increasing the sensitivity and specificity for task-based and resting state experiments at different field strengths. Multi-echo fMRI offers clear advantages for imaging brain regions such as the orbitofrontal cortex and inferior temporal lobes, which are prone to susceptibility distortions and signal dropouts (Halai et al, 2014; 2015). …”
Section: Denoising Methods Based On Multi-echo Fmrimentioning
confidence: 99%
“…As a result, the combined fMRI signal has a better contrast-to-noise ratio mainly due to the reduction in thermal noise, which can be exploited for increasing the sensitivity and specificity for task-based and resting state experiments at different field strengths. Multi-echo fMRI offers clear advantages for imaging brain regions such as the orbitofrontal cortex and inferior temporal lobes, which are prone to susceptibility distortions and signal dropouts (Halai et al, 2014; 2015). …”
Section: Denoising Methods Based On Multi-echo Fmrimentioning
confidence: 99%
“…Image acquisition and processing: Images were acquired on a 3T Siemens Prisma scanner using a 32-channel head coil. A dual-echo protocol was employed in which gradient-echo EPI images were simultaneously acquired at two TEs (13ms and 35ms) and a mean of the two echo series was computed during preprocessing (Halai, Parkes, & Welbourne, 2015). This approach improves signal quality in the ventral ATLs, which typically suffer from susceptibility artefacts (Ojemann et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…This method has recently been shown to out-perform single spin-echo imaging, and has also been shown to ameliorate "signal drop out", in temporal lobe regions (Halai, Welbourne, Embleton, & Parkes, 2014). Indeed, using this approach a recent study revealed selective responses to intelligible speech in inferior regions of the anterior temporal lobe, as well as more superior regions typically identified in studies of speech intelligibility (Halai, Parkes, & Welbourne, 2015).…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Since the establishment of fMRI over PET as the neuroimaging method of choice for studies of healthy brain function, this trend is strongly apparent in studies of speech comprehension. In general, the inferior temporal lobe has received relatively little attention in studies of speech, yet there are clues to its involvement in studies contrasting the perception of auditory speech at varying levels of intelligibility -for example, Adank's (2012) meta-analysis, which implicates a node in left fusiform gyrus, and Halai et al's (2015) finding of left inferior temporal and fusiform gyrus activation when employing dual-echo acquisition to reduce signal drop-out artefact. Beyond the issue of whether methodological limitations of fMRI have obscured the true apex of the temporal speech processing hierarchy in the ATL, the question arises as to whether this region reflects a language-specific response, or a domaingeneral semantic "hub" (Patterson et al, 2007).…”
Section: (C) Contextualising Perisylvian Responses To Intelligible Spmentioning
confidence: 99%
See 1 more Smart Citation